2019
DOI: 10.3390/su11092699
|View full text |Cite
|
Sign up to set email alerts
|

Integrated BIM-Parametric Workflow-Based Analysis of Daylight Improvement for Sustainable Renovation of an Exemplary Apartment in Seoul, Korea

Abstract: More than 60% of housing in South Korea consists of mass constructed apartment neighborhoods. Due to poor quality construction materials and components, the average operative life of apartment buildings is 20 years. The rapid degradation and low maintenance condition of transparent and semi-opaque components, as well as the limited daylight access in the standard apartment layout, are cause for the lower visual comfort of occupants. This research analyzes the improvement in visual comfort for the renovation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In fact, the main properties factors impacting the value depend also on elevation views, 3D geometry, orientation and the 3D location. For example, an apartment in the first floor isn't affected by the daylight factor in the same way as a one in the last floor [17]. Hence, the hedonic method needs to be enhanced in order to consider the real estate valuation in a 3D environment where houses are represented as 3D geometric and semantic objects.…”
Section: Hedonic Pricing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the main properties factors impacting the value depend also on elevation views, 3D geometry, orientation and the 3D location. For example, an apartment in the first floor isn't affected by the daylight factor in the same way as a one in the last floor [17]. Hence, the hedonic method needs to be enhanced in order to consider the real estate valuation in a 3D environment where houses are represented as 3D geometric and semantic objects.…”
Section: Hedonic Pricing Methodsmentioning
confidence: 99%
“…Building information modelling (BIM) has proven to be one of the major innovations in the building industry. By offering a rich 3D model with geometric, topologic and functional characteristics of the building at the conceptual design phase, opportunities to simulate some parameters related to different domains (energy, noise, property valuation, …) are improved [17].…”
Section: Bim Overviewmentioning
confidence: 99%
“…The context of existing and future residential structures for hydro-thermal modelling and monitoring tools was another subject for health monitoring [ 244 ]. The advantages of utilization BIM for monitoring and optimization of complex refurbishment cases were the main subject of various studies that investigated the barriers and research directions of this approach [ 121 , 245 , 246 , 247 , 248 , 249 ]. Okakpu et al [ 250 ] identified four dimensions that encompassed the impacts of BIM adoption specific to refurbishment projects and Becker et al [ 248 ] conducted research for data collection and actual modelling.…”
Section: Content Analysismentioning
confidence: 99%
“…The virtual reconstruction of the exemplar apartment analyzed in this study and the comfort simulations and analyses executed for both its existing and renovated states have been executed through the BIM-parametric renovation framework that has been described by the authors in previous studies [38,39]. Construction data and plans relative to the exemplary apartment building analyzed have been retrieved from the survey of the existing structure, and from literature on the history of housing in South Korea.…”
Section: Description Of the Bim-parametric Integrated Building Renovamentioning
confidence: 99%
“…Accordingly, the annual cumulative radiation for the building envelope has been analyzed using the Ladybug tools ( Figure 6). External factors, such as self-shading and shadows from neighboring buildings, and the Expressway, have been taken into account in the parametric analysis [38,39]. Accordingly, the unit located on the 7th floor (18 m) presents the average cumulative annual radiation values and has been selected for the energy simulation of technical heating and cooling loads and indoor comfort analysis of the occupants.…”
Section: Building Envelope Annual Cumulative Radiation Analysis and Smentioning
confidence: 99%